Effect of Intradialytic Exercise on Echocardiographic Findings in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2014)
Introduction. Cardiovascular disease is the major cause of death in hemodialysis patients. Regular aerobic or intradialytic exercise may play a role in reducing cardiovascular mortality in these patients. The aim of this study was to evaluate the relationship between intradialytic exercise and echocardiographic findings. Methods and Materials. Forty patients were enrolled in the study from Shahrekord Hemodialysis Center. They were randomly assigned into the exercise and control groups. In the exercise group, the patients had a 30-minute exercise program per dialysis session, 3 times a week, for 3 months. Electrocardiography and echocardiography were done at the beginning of the study and 3 months later. Results. The mean age and body mass index of the patients were 43.2 ± 10.5 years and 21.7 ± 5.4 kg/m2, respectively. Left ventricular ejection fraction increased and systolic pulmonary artery pressure and right ventricular size decreased significantly after the study in the exercise group patients. Conclusions. Our results showed the improvement of cardiac systolic and diastolic function in patients who had physical exercise during dialysis sessions. Regular intradialysis exercise can be suggested for hemodialysis patients without cardiac disease.